Penerapan Pastoral Konseling terhadap Perkembangan Rohani Bagi Jemaat di GMIM Martin Luther Warembungan - Mathew Mewo; Stansya Simon; Tamariska Tani; Tesalonika Pangkey; Natan Tene (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
Pastoral counseling is an essential aspect of church ministry aimed at supporting the spiritual growth of the congregation. This study aims to explore the role and importance of pastoral counseling in supporting the spiritual growth of the congregation at GMIM Marthin Luther Warembungan. Using a descriptive qualitative method, data were obtained through in-depth interviews with church leaders, pastoral counselors, and literature studies. The results of the study indicate that pastoral counseling plays a crucial role in helping congregants overcome various personal and spiritual issues, such as crises of faith, family problems, and emotional struggles. Effective pastoral counseling helps congregants find inner peace, strengthen their faith, and increase their involvement in church life. Additionally, trained pastoral counselors can provide the necessary emotional and spiritual support and guide congregants in their spiritual journey. This research confirms that pastoral counseling not only serves as a tool for problem resolution but also as a means to build a deeper relationship with God, enhance Biblical understanding, and facilitate spiritual transformation. Therefore, the church needs to pay more attention to developing comprehensive and sustainable pastoral counseling programs and ensure that pastoral counselors receive adequate training. Thus, pastoral counseling can become a strong foundation for the spiritual development and overall well-being of the congregation.